CAD/CAM and jewellery design education [abstract] - Roberta Bernabei; Alba Cappellieri (2015)
The paper will explore pedagogical methods for incorporating computer aided design and manufacture into higher education jewellery design. It seeks to identify weaknesses and strengths in contemporary teaching practices; highlighting innovative methods that nurture design problem solving, technical competence, exploration of new materials and dynamic form generation....